A systematic review of the use of adolescent mystery clients in assessing the adolescent friendliness of health services in high, middle, and low-income countries - Venkatraman Chandra-Mouli; Cosima Lenz; Emmanuel Adebayo; Iliana Lang Lundgren; Lucia Gomez Garbero; Subidita Chatteriee (Taylor & Francis Group, 2018)
Background: Mystery client methodology is a form of participatory research that provides a unique opportunity to monitor and evaluate the performance of health care providers or health facilities from the perspective of the service user. However, there are no systematic reviews that analyse the use of mystery clients in adolescent sexual and reproductive health (ASRH) research and monitoring and evaluation of programmes. Objective: To assess the use of adolescent mystery clients in examining health care provider and facility performance in providing ASRH services in high, middle, and low-income countries. Methods: We carried out a systematic review of published journal articles and reports from the grey literature on this topic from 2000 to 2017 (inclusive). Thirty research evaluations/studies were identified and included in the analysis. We identified common themes through thematic analysis. Results: The findings reveal that researchers and evaluators used mystery client methodology to observe client-provider relationships, and to reduce observation bias, in government or private health facilities, NGOs, and pharmacies. The mystery clients in the evaluations/studies were young people who played varying roles; in most cases, they were trained for these roles. Most reported good experiences and friendly providers; however, some reported lack of privacy and confidentiality, lack of sufficient written/verbal information, and unfavourable experiences such as sexual harassment and judgmental comments. Female mystery clients were more likely than males to report unfavourable experiences. Generally, the methodology was considered useful in monitoring and evaluating the attitudes of health service providers and ASRH service provision. Conclusions: The research evaluations/studies in this review highlight the usefulness of mystery clients as a method to gain insight, from an adolescent perspective, on the quality of ASRH services for research and monitoring and evaluation of programmes.